Development of Ce‐PSZ‐/Y‐PSZ‐Toughened Alumina Inserts for High‐Speed Machining Steel. Issue 2 (3rd October 2013) - Mondal, Biswanath; Mandal, Nilrudra; Doloi, Biswanath
<x xml:space="preserve">Abstract</x> The nanocomposite CeO2/Y2O3 partially stabilized zirconia (Ce‐PSZ/Y‐PSZ)‐toughened alumina was prepared by wet chemical simultaneous coprecipitation process. The thermal stability of phases and morphology of powders were characterized by TG‐DTA, FTIR, and FESEM. The microstructure, stabilization of phases and compositional analysis with different mol% CeO2/Y2O3‐doped zirconia in alumina are characterized by FESEM, XRD, and EDAX spectra. Significant improvement in fracture toughness and flexural strength has been observed in 10 vol% of partially stabilized zirconia (2.5 mol% Y2O3 in ZrO2/9 mol% CeO2 in ZrO2)‐toughened alumina, which is suitable for high‐speed machining applications.